Ablation behavior of graphene reinforced SiBCN ceramics in an oxyacetylene combustion flame. (November 2015) - Li, Daxin; Yang, Zhihua; Jia, Dechang; Duan, Xiaoming; He, Peigang; Zhou, Yu
Highlights: A protective oxide layer consisted of SiO2 and few B2 O3 was covered on ablation surface. Effect of graphene additionon ablation property and mechanisms of SiBCN matrix was studied. The ablation resistance of graphene reinforced ceramics exhibits a better performance than monolithic SiBCN. The main ablation mechanisms of graphene/SiBCN ceramics are thermal mechanical, chemical corrosion and mechanical denudation. Abstract: The effect of graphene on the ablation properties and microstructures of graphene reinforced SiBCN ceramics was investigated. A protective oxide layer mainly consisted of amorphous SiO2 glass and cristobalite is observed on ablation surface of all samples. Introduction of graphene provides superior thermal conductivity and a three-dimensional structure that significantly improves the ablation resistance compared to sample of SiBCN monoliths. Four ablation actions appeared to be responsible for observed ablation morphologies: oxidation of graphene and SiBCN matrix, erosion of graphene in ablation region, evaporation of gaseous products, flowing of SiO2 and B2 O3 by ablation steam.